1994
DOI: 10.1177/0148607194018002185
|View full text |Cite
|
Sign up to set email alerts
|

Anemia and Neutropenia Due to Copper Deficiency in Enteral Nutrition

Abstract: Copper deficiency has been regarded a rare complication of total parenteral nutrition. This report describes the first known case of anemia and neutropenia caused by copper deficiency in a patient receiving long-term enteral nutrition. A 34-year-old man presented with bulbar palsy and tetraplegia after an operation for cerebellar hemorrhage on June 7, 1989. Nasopharyngeal tube feeding with a defined-formula diet (Besvion) was instituted on June 19, 1989. He developed normocytic anemia and neutropenia approxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 10 publications
0
22
0
Order By: Relevance
“…7 To our knowledge, there have been only 2 previous reports 4,5 of copper deficiency due to intestinal malabsorption after partial gastrectomy in patients who, like our patient, were not receiving parenteral or enteral nutrition. One of these patients 5 also had neurologic abnormalities.…”
Section: Resultsmentioning
confidence: 57%
“…7 To our knowledge, there have been only 2 previous reports 4,5 of copper deficiency due to intestinal malabsorption after partial gastrectomy in patients who, like our patient, were not receiving parenteral or enteral nutrition. One of these patients 5 also had neurologic abnormalities.…”
Section: Resultsmentioning
confidence: 57%
“…Previous studies have reported that copper-deficient anemia by adequate copper supplementation gradually improved after three months and neutrophil counts also returned to normal within 2-4 weeks (13,14). …”
Section: Introductionmentioning
confidence: 83%
“…Reports of adults receiving feeding via a nasopharyngeal tube or long-term enteral nutrition with a jejunostomy were diagnosed with copper deficiency as determined by low blood copper and ceruloplasmin levels. 20,21 There were no reports of bone abnormalities in these adults. Children receiving either total parenteral nutrition or some type of enteral nutrition are especially vulnerable to copper deficiency.…”
Section: Copper and Bonementioning
confidence: 95%